Um modelo dos fatores que influenciam a satisfação dos torcedores na ida aos estádios de futebol no Brasil e sua intenção de retorno - Andre Francisco Alcantara Fagundes (2013)
This study aimed to examine how emotional factors and factors related to social relations, and infrastructure and sports product factors, influence football fan satisfaction and their intention of returning to the football stadium. Several studies on sports consumption (MADRIGAL, 1995; MORGAN; SUMMERS, 2008; MULIN; HARDY; SUTTON, 2004) suggest that, compared to other types of consumption, in this specific modality, the emotional/affective aspect stands out most significantly. Therefore, it is considered that this study is justified and supported by the following aspects: (a) the particular characteristics of sports consumption, suggesting greater influence of the emotional/affective dimension in the behavior of this type of consumer; (b) the lack of academic studies in Brazil on this type of consumption; (c) the management and social relevance of understanding the behavior of football and sports fans; (d) the importance of sport as an economic sector; (e) the small amount of fans attending the stadiums in the country to watch football games; and (e) the special circumstance in which Brazil is, hosting two major world sporting events in the coming three years e the FIFA World Cup, to be held in 2014, and the Rio de Janeiro Olympic Games, scheduled for 2016. From this scenario, we propose a theoretical model containing the possible factors that influence the frequency of football fans in Brazilian stadiums. For this purpose, we chose to analyze the following constructs related to emotional factors and factors related to social relations: identification with the team, team loyalty, positive emotions and socialization of the fans in the stadium. In turn, the constructs related to infrastructure and sports product factors used were: quality of services at the stadium, ticket pricing, ticket accessibility, performance of the team in the league and importance of the game. These constructs were related to fans satisfaction and, finally, with the intention of returning to the stadium. The adopted method involved two main empirical stages. The first one consisted of an exploratory qualitative research in the form of three focus groups with Brazilian football fans, aiming to understand the reasons why these consumers attend the stadiums. The second one tested the twelveproposed hypotheses, presenting a quantitative approach. To collect the data for this stage, an electronic survey was used. The chosen statistics technique was Structural Equation Modeling (SEM). 1.932 responses were considered valid for the study. The survey results confirmed eight of the proposed hypotheses. The tests undertaken in the model showed its empirical adjustment and validity. Afterwards, this model was compared with two rival models in order to find the most adjusted one, and Rival Model 2 presented the best adjustment indices. Based on the squares of correlations (R2) obtained in this model, it could be concluded that the antecedent variables of intention of returning to the stadium explain 30,2% of its variance. On the order hand, the antecedent variables of satisfaction explain 28,0% of its variance. Finally, seeking to respond to the overall objective, we analyzed the influence of the two groups ofdifferent factors on satisfaction and intention of returning to the stadium. As main results, it was found that emotional factors and factors related to social relations influenced more significantly on both satisfaction and intention of returning to the stadium than infrastructure and sports product factors.